English Teacher’s Questioning Strategies in EFL Classroom at SMAN 1 Bontomarannu - Sujariati Sujariati; Andi Qashas Rahman; Murni Mahmud (ELT Worldwide: Journal of English Language Teaching, 2016)
The objectives of this research were to find out the teacher’s questioning strategies, the reasons of using the questioning strategies, and the effects of the questioning strategies on student’s learning activities. The samples of this research were the teachers of senior high school in Gowa (SMAN 1 Bontomarannu). The approach employed in this research was qualitative one. The type of this research belongs to discourse analysis. Data collection of this research was conducted through recording, observation, and interview. The data gathered were analyzed through conversation analysis which were used in analyzing teacher’s questioning strategies, the reasons and the effects on students learning activities in EFL classroom. The research findings showed that the teacher used questioning strategies by applying some type of questions and performing the type of questions in each session of teaching. The open/closed questions and display questions were the dominant, it depends on the material that the teacher transferred to the students. Otherwise, the recall and referential questions, it used only a few times by teacher. The teacher also was applying other strategies, it was repeated the questions, emphasis the question, translated into Bahasa Indonesia or mixed the questions, get closer to student, and gave reward to the students. The research finding showed the positive effects from the use of questioning strategies which were applied by the teachers in EFL Classroom. It was proved by many responses from the students. Moreover, it was proved by the observation that both the teacher and the students did a good interaction through questioning strategies. Key words: English teacher’s questioning and Strategies